2006
DOI: 10.1086/503016
|View full text |Cite
|
Sign up to set email alerts
|

Limiting the Emergence of Extended-Spectrumβ–Lactamase-Producing Enterobacteriaceae: Influence of Patient Population Characteristics on the Response to Antimicrobial Formulary Interventions

Abstract: The effect of antimicrobial formulary interventions intended to curb emergence of ESBL-EK may differ substantially across institutions, perhaps as a result of differences in patient populations. Variability in the epidemiological profiles of ESBL-EK isolates at different hospitals must be considered when designing interventions to respond to these pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…A quasiexperimental design that attempts to control for confounding is the one-group pretest-posttest design with a nonequivalent dependent variable (154,155). For example, Gottesman et al observed a decline in fluoroquinolone-resistant E. coli in urine cultures during a community intervention in which preapproval was required to prescribe ciprofloxacin (155).…”
Section: Nonrandomized Intervention (Quasiexperimental or Beforeaftermentioning
confidence: 99%
“…A quasiexperimental design that attempts to control for confounding is the one-group pretest-posttest design with a nonequivalent dependent variable (154,155). For example, Gottesman et al observed a decline in fluoroquinolone-resistant E. coli in urine cultures during a community intervention in which preapproval was required to prescribe ciprofloxacin (155).…”
Section: Nonrandomized Intervention (Quasiexperimental or Beforeaftermentioning
confidence: 99%
“…Surprisingly, this amount of meropenem reduction needed for an effective impact on 34MRGN-PA incidence is relatively small. In two reports, implementation of ASPs resulted in a 54% to 97% decrease of the targeted antimicrobial agents over a study period of 3 to 5 years (26,27). According to our results, such intensive restriction may not be necessary in all cases, especially as countereffects could be a consequence.…”
Section: Discussionmentioning
confidence: 50%
“…In previous research, a decrease in resistant pathogens, such as Clostridium difficile [18], extended-spectrum β-lactamase-producing E. coli and K. pneumonia [19], and methicillin-resistant Staphylococcus aureus (MRSA) [21] was noted. Decreases in hospital stays [22] and improvements in successful treatments [20] have also been reported.…”
Section: Discussionmentioning
confidence: 95%
“…Prospective antimicrobial audits and feedback systems have also shown benefits such as cost-effectiveness [17], reductions in the inappropriate antibiotic prescriptions [10], decreases in antimicrobial consumption [18][19] and "bug-drug" mismatch [20].…”
Section: Discussionmentioning
confidence: 99%